The IMF and The Poor. (Pamphlet Series; Pamphlet Series, ;, 1999)
The IMF is increasingly emphasizing "high-quality growth" - that is, growth that is sustainable, that is accompanied by appropriate domestic and external balances, that respects the environment, and that is aided by policies that reduce poverty and foster greater equity. This pamphlet focuses on how the IMF works to reduce poverty and improve equity.